Effects of cryopreservation on sperm subpopulations in goats - Hernández Corredor, Leonardo (2018)
The aim of this study was to evaluate the effect of cryopreservation in the presence of sperm subpopulations, according to motility, in sperm ejaculates using the Computer Assisted Semen Analysis (CASA) system. The motility parameters were analysed with principal component analysis (PCA) where they showed the highest variance, thus reducing the number of variables. In the evaluation of 23 738 fresh spermatozoa, the subpopulation (Sp) 1 consisted of progressive spermatozoa and median progressive motility (18.34%), Sp 2 in high velocity and progressive spermatozoa (20.53%), Sp 3 in high-activity spermatozoa, but not progressive (46.79%) and Sp 4 in little activity and non-progressive spermatozoa (14.32%), showing significant differences in the distribution of the four Sp (p<0.001). The structure of the spermatozoa Sp was not maintained after freezing. When evaluating the same parameters in thawed samples in 36 450 motile sperm, the Sp 1 consisted of slow and linear slow progressive spermatozoa (38.43%), the Sp 2 in slowly active and slow spermatozoa (7.3%), the Sp 3 in spermatozoa with high activity and excellent progressive motility (11.65%) and Sp 4 in active spermatozoa, but not progressive (42.61%), showing significant differences in the distribution of the four Sp (p<0.001). Cryopreservation significantly modified both the specific parameters and the distribution of the spermatozoa within the subpopulations.